Multiple GmWRI1s are redundantly involved in seed filling and nodulation by regulating plastidic glycolysis, lipid biosynthesis and hormone signalling in soybean (Glycine max) - Chen, Beibei (Plant Biotechnol J, 2019)
It has been reported that lipid biosynthesis in plant host root cells plays critical roles in legume‐fungal or ‐rhizobial symbioses, but little is known about its regulatory mechanism in legume–rhizobia interaction. Soybean WRINKLED1 (WRI1) a and b, with their alternative splicing (AS) products a’ and b’, are highly expressed in developing seeds and nodules, but their functions in soybean nodulation are not known. GmWRI1a and b differently promoted triacylglycerol (TAG) accumulation in both Arabidopsis wild‐type and wri1 mutant seeds and when they ectopically expressed in the soybean hairy roots. Transcriptome analysis revealed that 15 genes containing AW boxes in their promoters were targeted by GmWRI1s, including genes involved in glycolysis, fatty acid (FA) and TAG biosynthesis. GmWRI1a, GmWRI1b and b’ differentially transactivated most targeted genes. Overexpression of GmWRI1s affected phospholipid and galactolipid synthesis, soluble sugar and starch contents and led to increased nodule numbers, whereas GmWRI1 knockdown hairy roots interfered root glycolysis and lipid biosynthesis and resulted in fewer nodules. These phenomena in GmWRI1 mutants coincided with the altered expression of nodulation genes. Thus, GmWRI1‐regulated starch degradation, glycolysis and lipid biosynthesis were critical for nodulation. GmWRI1 mutants also altered auxin and other hormone‐related biosynthesis and hormone‐related genes, by which GmWRI1s may affect nodule development. The study expands the views for pleiotropic effects of WRI1s in regulating soybean seed filling and root nodulation.